2023
DOI: 10.3390/biology12081139
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Pathophysiology of Traumatic Brain Injury: What Have We Learned So Far?

Marco Aurelio M. Freire,
Gabriel Sousa Rocha,
Leonardo Oliveira Bittencourt
et al.

Abstract: Traumatic brain injury (TBI) is one of the leading causes of long-lasting morbidity and mortality worldwide, being a devastating condition related to the impairment of the nervous system after an external traumatic event resulting in transitory or permanent functional disability, with a significant burden to the healthcare system. Harmful events underlying TBI can be classified into two sequential stages, primary and secondary, which are both associated with breakdown of the tissue homeostasis due to impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 221 publications
0
14
0
Order By: Relevance
“…These events could occur in sports or various types of professions, as well as in violence, accidents, or falls [ 19 ]. Penetrating or non-penetrating brain trauma could be the result of focal penetration of foreign objects, blunt force, jolts, jerks, bumps, or blasts [ 20 ]. The pathological processes underlying TBI are direct or indirect consequences of the brain trauma and include tissue deformation and focal damage (skull, meninges, or brain), as well as blood-brain barrier and brain blood flow disturbance, molecular imbalance associated with necrosis and apoptosis, oxidative stress, and inflammation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These events could occur in sports or various types of professions, as well as in violence, accidents, or falls [ 19 ]. Penetrating or non-penetrating brain trauma could be the result of focal penetration of foreign objects, blunt force, jolts, jerks, bumps, or blasts [ 20 ]. The pathological processes underlying TBI are direct or indirect consequences of the brain trauma and include tissue deformation and focal damage (skull, meninges, or brain), as well as blood-brain barrier and brain blood flow disturbance, molecular imbalance associated with necrosis and apoptosis, oxidative stress, and inflammation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These variations likely reflect the adaptation of protoplasmic astrocytes to the characteristic loss of cell polarity and disruption of tissue organization within the damaged neural network at the primary injury site. Following a TBI, many processes such as cell death, neuroinflammation, cell proliferation, and tissue repair overlap to one another, resulting in loss of astrocyte subpopulations and the formation of astrocyte borders, where newly formed astrocytes demarcate and separate damaged areas from the healthy surrounding tissue (Burda et Sofroniew, 2014; Wahane et Sofroniew, 2022; Freire et al, 2023). Interestingly, we found that not only protoplasmic astrocytes, but also pial and juxtavascular astrocytes experienced morphological changes in response to the injury (reactivity) that integrated shape- and size-related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, secondary injury is a complex occurrence that happens seconds or months after primary injury. Symptoms such as neuroinflammation, blood-brain barrier (BBB) disruption, increased intracranial pressure, cerebral edema, mitochondrial dysfunction, oxidative stress, excitotoxicity, metabolic dysfunction, and cerebral ischemia develop over time (Abdul-Muneer et al, 2015;Freire et al, 2023;Postolache et al, 2020;Winkler et al, 2016). ROS production determines the course of secondary injury, and oxidative stress biomarkers accumulate (Davis & Vemuganti, 2022;Hergenroeder et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A physical impact on the skull may cause Traumatic Brain Injury (TBI) with high mortality and morbidity rates (Freire et al, 2023). Approximately 70 million people suffer from TBI annually; Around 81% of these cases are mild, 11% moderate, and 8% severe (Dewan et al, 2018;Freire et al, 2023). TBI is triggered by a sudden impact and results in complex pathophysiological events, depending on the location of the effect.…”
Section: Introductionmentioning
confidence: 99%